Technological Transformation of Health Innovation “SiKemBang” as a Decision-Support Tool for Post-Partum Family Planning - Herni Kurnia; Nunung Mulyani; Endang Astiriyani (Jurnal Medisci, 2026)
Background: Maternal Mortality Rate (MMR) remains a major health problem in Indonesia (189 per 100,000 live births, 2020 Population Census), and family planning (FP) is one of the four pillars of the safe-motherhood approach used to reduce it, particularly by preventing pregnancies that are too young, too frequent, too closely spaced, or too late. The Balanced Counseling Strategy (BCS) for post-partum FP improves the accuracy of provider-client interaction but conventionally requires carrying three separate job aids. Aim: To design and test the effectiveness of “SiKemBang”, an Android-based application that integrates the BCS job aids as a decision-support tool for post-partum FP. Methods: A Research and Development (R&D) design following Sugiyono’s model was used, involving midwives and post-partum mothers at PONED facilities in Tasikmalaya City, with material- and media-expert validation followed by small- and large-scale field trials. Results: The application was developed and revised until it was rated highly feasible by both material and media experts without further revision; the small-scale trial (n = 10) produced a mean score of 46.9 (93.8%) and the large-scale trial (n = 100) produced a mean score of 482 (96.4%), both in the “highly feasible” category. Conclusions: SiKemBang is a feasible and effective decision-support tool for post-partum FP counseling. Implication: The application can strengthen health-technology-based counseling services and support national efforts to reduce maternal and infant mortality.